A function is given f(x)=2x4−3x3+4x2−5x+6f(x)= 2x^{4} - 3x^{3} + 4x^{2} - 5x +6f(x)=2x4−3x3+4x2−5x+6, calculate the sum of S=A+B+C+D+ES= A+B+C+D+ES=A+B+C+D+E , if f(x)=A(x−1)4+B(x−1)3+C(x−1)2+D(x−1)+Ef(x)= A(x-1)^{4} + B(x-1)^{3} + C(x-1)^{2} + D(x-1) +Ef(x)=A(x−1)4+B(x−1)3+C(x−1)2+D(x−1)+E
Note by Sopheak Seng 7 years, 3 months ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Make the substitution x = z - 1 and expand f(x) to get 2z^5 + 5z^4 + 7z^2 + 2z + 4. Hence, S = 2 + 5 + 7 + 2 + 4 = 20.
Log in to reply
Wouldn't we take x=z+1 x = z + 1 x=z+1. Because If x=z−1 x = z - 1 x=z−1, we'd have x+1=z x + 1 = z x+1=z and the f(x) you got would be 2(x+1)5… 2(x+1)^5 \ldots 2(x+1)5….
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Make the substitution x = z - 1 and expand f(x) to get 2z^5 + 5z^4 + 7z^2 + 2z + 4. Hence, S = 2 + 5 + 7 + 2 + 4 = 20.
Log in to reply
Wouldn't we take x=z+1. Because If x=z−1, we'd have x+1=z and the f(x) you got would be 2(x+1)5….